Upaya Peningkatan Perempuan dalam Berwirausaha pada Sektor UMKM Melalui Social Entrepeneurship (Studi pada Perempuan di Kecamatan Rembang Kabupaten Pasuruan) - Rosa Silma Nubaila; Miftahul Huda (Journal of Management and Bussines (JOMB), 2024)
This research aims to describe efforts to increase women's entrepreneurship in Micro, Small and Medium Enterprises (MSMEs) through the concept of Social Entrepreneurship in Rembang District. This research uses a descriptive qualitative approach. Data was obtained through direct interviews with several samples selected from the population, calculated using the Slovin formula. The results of the research show that the five business models (Entrepreneurial Opportunities, Entrepreneurial Skills, Women Empowerment, Marketing Orientation, and Networking) that have been implemented in Rembang District are effective solutions in overcoming challenges as well as being social innovations that play an important role in increasing the efforts of women in Rembang District in entrepreneurship. In conclusion, this research provides further understanding regarding efforts to increase women's entrepreneurial skills in facing the impact of the pandemic, focusing on the social and environmental context of Rembang District. Keywords: MSMEs, Women Entrepreneurs, Entrepreneurship